A geological perspective on calcareous nannoplankton evolution : biotic response to global change and environmental perturbations? - E. Erba; C. Bottini; C.E. Casellato; B. De Bernardi; D. Tiraboschi (null, 2008)
Recent environmental changes and climate instabilities pose urgent questions regarding biota ability to keep pace with concurrent excess CO2, global warming and ocean acidification. Major concerns are addressed to the possibility of near future extinctions causing a biodiversity loss and revealing a biota failure in sustaining rapid and progressive environmental changes accelerated by anthropogenic impacts. However, the findings of new organisms in various ecosystems raise the possibility that global change might stimulate biota speciation and/or innovation: novel life forms might represent temporary adaptation to environmental stress or might be real new species evolved in response to global change. The ocean, the oldest and largest ecosystem on Earth, best recorded global changes in climate and oceanic physical, chemical and trophic parameters. Within the oceanic biosphere, calcareous phytoplankton plays a special role as: (1) is common and widespread and consists of cosmopolitan and endemic taxa; (2) has a 220 My-long evolutionary history; (3) is one the most effective calcite producers of the planet since the Jurassic; (4) is relevant for both the inorganic and organic carbon cycle; (5) is extremely sensitive to environmental variations; (6) may directs climate change by altering albedo and absorption/ emission of atm-CO2 at large scale. The Phanerozic geological record of global change unambiguously indicates that the Earth system already experienced conditions of (super)greenhouse and (super)icehouse. Diversity pulses of calcareous nannoplankton are grossly coeval with major events such as climate and sea-level changes, large magmatic episodes and variations in ocean structure and composition, suggesting that evolutionary patterns are intimately linked to environmental modifications. Our study aims at reconstruction of both tempo and mode of nannoplankton evolution and the causal/casual role of environmental pressure. We explored time-intervals of (1) evolutionary acceleration in absence of coeval ...